The Impact Of Implementing The Independent Curriculum On Students' Learning Interest In The Subjects Of Pancasila And Citizenship Education At SMK Negeri 17 Samarinda - Ariani Songli; Wingkolatin, Wingkolatin; Marwiah Johansyah; Novita Majid (Jurnal Scientia, 2024)
Pancasila and Citizenship education has an important role in shaping students' character and national insight. However, this subject is often considered less interesting by some students because the teaching methods tend to be monotonous and less relevant to everyday life. The aim of this research is to find out how the Merdeka curriculum is implemented on students' interest in learning in Civics subjects at SMK Negeri 17 Samarinda, then what impacts occur in implementing the Merdeka curriculum on students' interest in Civics subjects at SMK Negeri 17 Samarinda, and what efforts are made what can be done to deal with the impact of implementing the Independent Curriculum on students' interest in learning in Civics subjects at SMK Negeri 17 Samarinda. Type of descriptive qualitative research. The research was conducted at SMK Negeri 17 Samarinda in July 2024-September 2024. The subjects of this research were curriculum cadets, PPKn teachers, and students in classes X, XI, XII using observation, interview and documentation techniques. Data analysis techniques are data collection, data reduction, data presentation, and data conclusion. The results of the research show that the method of implementing the independent curriculum is able to increase students' interest in learning in civics subjects at SMK Negeri 17 Samarinda. The impact of this method of implementing the independent curriculum is very clear from the aspect of student participation in the teaching and learning process, the components in the independent curriculum are very helps in increasing student participation in civics subjects, and this method makes it easier for teachers when teaching and also makes it easier for students to receive and understand the lesson material.